2004
DOI: 10.1002/cncr.20383
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of place of death for Japanese patients with advanced‐stage malignant disease in home care settings: A nationwide survey

Abstract: BACKGROUNDAlthough the place of death for patients with advanced malignancy is influenced by multiple factors, few studies have systematically investigated the determinants of place of death. The objective of the current retrospective study was to clarify the predictors of home death throughout the duration of home palliative care for Japanese patients with advanced malignant disease.METHODSIn the current nationwide survey, the authors investigated predictors involving patient demographics and clinical profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
2
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 27 publications
6
80
2
6
Order By: Relevance
“…The rate found in this study is also similar to the results reported by Fukui et al [10] who found that among a sample of 428 Japanese patients receiving palliative care at home, 64.8% subsequently died in their own homes.…”
Section: Discussionsupporting
confidence: 93%
“…The rate found in this study is also similar to the results reported by Fukui et al [10] who found that among a sample of 428 Japanese patients receiving palliative care at home, 64.8% subsequently died in their own homes.…”
Section: Discussionsupporting
confidence: 93%
“…6,7,9 Since addressing this important association was not an aim of this study and the finding came from an adjustment in the analysis of community nurses' involvement, no conclusion can be made and the found association therefore deserves further investigation.…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
“…5 However, studies indicate that GP involvement is associated with facilitating home death. [6][7][8][9] Furthermore, despite earlier studies identifying considerable dissatisfaction with symptom control in a primary care setting, 3,10 satisfaction with GPs was still rated high 3 and relatives valued the involvement of GPs. 11,12 All in all, it suggests that good palliative care amounts to more than simply a certain degree of symptom control.…”
Section: Introductionmentioning
confidence: 99%
“…Negative beliefs about palliative care were also one of the significant determinants of the potential underuse of specialized palliative care services [8][9][10][11][12]. Moreover, many patients have concerns and difficulties about homecare, such as the burden on the family, concerns about sudden changes in physical conditions, and the unavailability of physicians visiting their home, and these could influence patients' decisions regarding whether or not to receive homecare [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, multiple empirical studies have identified knowledge, beliefs, or concerns about opioids, palliative care, and homecare in the general population and cancer patients as potential barriers for quality palliative care [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Many surveys have shown that incorrect knowledge about cancer pain and opioids could interfere with optimal pain management, especially an unrealistic fear of addiction and life-shortening [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%